Pengaruh Budaya Oragnisasi, Motivasi Intrinsik, Motivasi Ekstrinsik Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada UPTD Puskesmas Rawat Inap Kotagajah. - Kurniyanti, Rizka Minda; Siswoyo, Slamet Tedy (Jurnal Manajemen DIVERSIFIKASI, 2022)
ABSTRACT Rizka Minda Kurniyanti, The Influence of Organizational Culture, Intrinsic Motivation, Extrinsic Motivation and Job Satisfaction on Employee Performance at the UPTD of the Kotagajah Inpatient Health Center. Supervisor (1) H. Suwarto2, S.E M.M, Fitriani2 S.E., M.M. Companies definitely need competent and qualified employees, especially in this era of globalization. All business organizations are the driving force in decisions to achieve organizational goals. Organizational development is determined by the work of HR in the organization. This study aims to determine 1) To find out whether organizational culture has an effect on employee performance. 2) To find out whether Extrinsic Motivation has an effect on employee performance. 3) To find out whether Intrinsic Motivation has an effect on employee performance. 4) To find out whether job satisfaction has an effect on employee performance. 5) To find out whether organizational culture, extrinsic motivation, intrinsic motivation, and job satisfaction together affect employee performance. This study uses a quantitative approach. The survey method was chosen as the primary data source. The survey method focuses on collecting data from respondents who have certain information, thus enabling researchers to solve problems. In this study, the population of this study were employees and some students who were intern at the UPTD Inpatient Health Center Kotagajah were 84 people. The results showed that 1) there was a positive and significant influence between organizational culture on employee performance. 2) there is a positive and significant influence between Extrinsic Motivation on employee performance. 3) there is a positive and significant influence between intrinsic motivation on employee performance 3) there is a positive and significant influence between job satisfaction on employee performance 4) there is a positive and significant influence between organizational culture, extrinsic motivation, intrinsic motivation, and job satisfaction on performance employee. keywords : Reliability, Responsiveness, Physical evidence and customer satisfaction